GIS-material for the archaeological project: Stone Age remains at Marmorbruket - Swedish National Heritage Board, UV Öst (Uppsala University, 2014)
The information in the abstract is translated from the archaeological report:
Due to planned water and sewer pipes at Marmorbruket, east of Krokek, Norrköping municipality, the Swedish National Heritage Board's contract archaeology division, UV Öst, performed a preliminary investigation in May 2005, since the area is close to a Pitted Ware settlement by Fagervid. In the test trenches, stray finds of worked quartz and other rock were found. The trenches covered what was interpreted as the outskirts of a small, Mesolithic settlement located by the shore. At the investigation occasion, trenching for the pipes was already taking place. UV Öst believes the centre of the settlement was located in the area already excavated for the pipes. The settlement might though have extensions in the surrounding areas to the north and west. An inspection of the surrounding area was also made in order to deepen the understanding of the place. Another Stone Age settlement was then found c. 200 m NNW of the investigation area. UV Öst suggests no further measures in this stage, but points out the high possibility of finding still more Stone Age settlements in the area.

Purpose:

The information in the purpose is translated from the archaeological report:
The purpose of the preliminary investigation was to examine whether the settlement extended to the hillsides in north-east. If so, finds and samples were to be collected and analysed in order to establish the preservation situation and the scientific potential of the site. Another aim was to investigate whether earlier settlement stages were preserved higher up in the terrain.

The ZIP file consist of GIS files and an Access database with information about the excavations, findings and other metadata about the archaeological survey.

Informationen i sammanfattning är hämtad ur rapporten för undersökningen:
På grund av planerad utbyggnad av vatten och avlopp vid Marmorbruket, öster om Krokek, Norrköpings kommun, genomförde RAÄ UV Öst en arkeologisk förundersökning i maj 2005, då platsen ligger i nära anslutning till den gropkeramiska boplatsen vid Fagervik. I sökschakten hittades spridda bitar bearbetad kvarts och bergart. Schakten berörde vad som bedöms vara utkanten på en mindre, strandbunden mesolitisk boplats. Vid undersökningstillfället pågick markarbeten i direkt anslutning till den planerade VA-ledningen. UV Öst bedömer att boplatsens centrum återfinns där man redan hunnit schakta bort de fyndförande lagren. Boplatsen kan dock ha en fortsättning i omkringliggande områden mot norr och väst. En besiktning av närområdet gjordes också för att öka platsförståelsen. En annan stenåldersboplats påträffades drygt 200 m NNV om undersökningsområdet. UV Öst föreslår inga fortsatta arkeologiska åtgärder i detta skede, men påpekar att möjligheterna att hitta fler stenåldersboplatser i närområdet bedöms som höga.

Syfte:

Informationen i syfte är hämtad ur rapporten för undersökningen:
Syftet med förundersökningen var att undersöka huruvida boplatsen bredde ut sig i sluttningarna mot nordost. Om så var fallet skulle fynd och prover samlas in för vidare analys av bevaringsförhållandet och det vetenskapliga källäget. Ett annat syfte var att undersöka om äldre bosättningsfaser fanns representerade längre upp i terrängen.

ZIP-filen innehåller GIS-filer samt en Access datafil vilka innehåller information om schakt, fyndföremål, lämningstyper samt annan metadata om den arkeologiska undersökningen.
GIS-material för arkeologiskt projekt: Stenålder vid Marmorbruket
Keywords: Mesolithic; mesolitikum; HISTORY; HISTORIA; History and Archaeology; Historia och arkeologi; Archaeology; Arkeologi